DINAMIKA TAKTIS PERGANTIAN PEMAIN DAN STABILITAS PERTAHANAN: ANALISIS TEMPORAL KELELAHAN FISIK DAN KOGNITIF PADA LIGA PROFESIONAL INDONESIA - Rodhi Rusdianto Hidayat; Evi Sinaga; Miftah Fariz prima Putra (Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study presents a comprehensive analysis of the tactical dynamics of player substitutions and their impact on defensive stability in professional football. Utilizing a retrospective observational approach on macro-event data from a full competitive season, this research dissects the temporal distribution of goals, yellow cards, and coaching interventions grouped into six time intervals. The analysis reveals a significant home advantage bias, where away teams bear a substantially higher burden of disciplinary sanctions as a manifestation of psychological pressure and situational anxiety induced by the crowd, a phenomenon empirically shown to influence referee cognition. Crucial findings highlight a non-linear escalation during the final match phase (minutes 76–90+'), where the rate of goals conceded (23.9%) peaks concurrently with a surge in defensive fouls (33.1%). This phase coincides with the highest concentration of substitutions (40.6%), indicating a temporal mismatch. Coaching interventions prove to be reactive to the collapse of defensive organization caused by glycogen depletion and cognitive fatigue. Furthermore, the study dissects the phenomenon of reverse causality based on game state, where early substitutions correlate with late-game offensive productivity but are predominantly triggered by initial tactical deficits. The conclusions demand a paradigm shift in coaching towards proactive fatigue mitigation.